2017
DOI: 10.1002/aoc.3893
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐opening polymerization of lactide, ε‐caprolactone and their copolymerization catalyzed by β‐diketiminate zinc complexes

Abstract: A series of zinc silylamido complexes bearing non-symmetric β-diketiminate ligands were synthesized and structurally characterized. Ring-opening polymerization (ROP) of rac-lactide catalyzed by these zinc complexes afforded heterotactic polylactides at room temperature (P r = 0.79~0.83 in THF). The steric and electronic characteristics of the ancillary ligands showed significant influence on the polymerization performance of the corresponding zinc complexes. All these zinc complexes also showed moderate activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 71 publications
2
20
0
2
Order By: Relevance
“…In contrast, previous results showed that, although the active PLL did initiate CL in a sequential copolymerization, the resulting copolymer had more of a random/statistical distribution of monomers than would be expected for a block copolymer microstructure . This was attributed to the occurrence of transesterification reactions caused by the CL‐derived hydroxyl end‐groups generated during the second‐step copolymerization, as also observed by other workers …”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In contrast, previous results showed that, although the active PLL did initiate CL in a sequential copolymerization, the resulting copolymer had more of a random/statistical distribution of monomers than would be expected for a block copolymer microstructure . This was attributed to the occurrence of transesterification reactions caused by the CL‐derived hydroxyl end‐groups generated during the second‐step copolymerization, as also observed by other workers …”
Section: Resultsmentioning
confidence: 64%
“…In other previous studies, a P(CL‐ b ‐LL) block copolymer was prepared via a two‐step polymerization in which PCL was generated as a prepolymer in the first step. Reversal of the monomer addition using a PLL prepolymer as the propagating species gave a more random structure which was attributed to increased transesterification during copolymerization . Other researchers have also attempted to synthesize P(LL‐ b ‐CL) using PLL as a propagating species, employing either rare earth metal based initiators or specially designed, sterically hindered tin(IV) initiators .…”
Section: Introductionmentioning
confidence: 99%
“…在本组之前的工作中, 我 们合成了一系列基于非对称 β-二亚胺配体的锌硅氨基 络合物, 对外消旋丙交酯和 ε-己内酯聚合表现出较高的 催化活性, 并可催化两种单体共聚主要得到两嵌段共聚 物 [72] . 在此基础上, 本文进一步设计合成了相应的非对 称 β-二亚氨基镁络合物, 系统研究了配体其中一个 N-芳基为 2,6-二异丙基苯基、同时在另一个 N-芳基上引入 具有较小位阻效应的供电子或吸电子基团时, 该类取代 基因素对镁络合物催化外消旋丙交酯、ε-己内酯开环聚 合及 L-丙交酯和 ε-己内酯共聚性能的影响.…”
Section: β-二亚胺配体因其合成简单 很容易通过改变苯胺 上的取代基以调整金属周围的空间位阻和电子性质 故 广泛用于与不同的金unclassified
“…(见图 1)主要参照文献 方法合成 [37,72] ; 镁硅氨基络合物 1~7 的合成路线如图 1 [72] , 这一点与对称取代 β-二亚氨基锌、 镁络合物中的规律一致 [48,49] . 镁金属中心与配体骨架中 [49,50,56] , 说明在固体 Figure 2 The molecular structure of complex 1 [68] .…”
Section: 镁络合物的合成 非对称 β-二亚胺配体 Hl 1~7unclassified
“…Many metal complexes have been explored for catalytic (co)polymerization of lactide, such as tin, [9][10][11] lanthanum, [12,13] aluminum, [14,15] zinc [16][17][18][19] and zirconium. [20][21][22][23] It is well known that stannous octoate Sn(Oct) 2 is the most popular catalyst in polymerization of lactide for its high efficiency.…”
Section: Introductionmentioning
confidence: 99%